2018
DOI: 10.1177/1538574418814612
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Use of Biochemical Markers in the Assessment of Spinal Cord Ischemia in Thoracoabdominal Aortic Aneurysm Repair

Abstract: Introduction: Despite advances in perioperative critical care and surgical technique, spinal cord ischemia remains a devastating complication of thoracic and thoracoabdominal aortic aneurysm repair. Biochemical markers present in peripheral blood and cerebrospinal fluid (CSF) may be useful in assessing spinal cord injury. We systematically analyze and report the role of all reported biochemical markers that have been used in assessing and diagnosing spinal cord ischemia in thoracic and thoracoabdominal aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…There have been 33 meta‐analyses on the wealth of data on Nf as a biomarker for neurodegeneration over the past 15 years (Agah et al, 2018; Alagaratnam, Widekind, et al, 2021; Angelopoulou et al, 2021; Arneth & Kraus, 2022; Cai & Huang, 2018; Choong et al, 2019; Cong et al, 2021; Forgrave et al, 2019; Gao et al, 2020b; Ge et al, 2018; Hoiland et al, 2022; Hu et al, 2017; Jin et al, 2019; Karantali, Kazis, Chatzikonstantinou, et al, 2021; Karantali, Kazis, McKenna, et al, 2021; Katayama et al, 2020; Koychev et al, 2021; Li et al, 2016; Liu et al, 2022; Liu, Chen, et al, 2020; Martin et al, 2019; Mondello et al, 2021; Peng et al, 2022; Petzold et al, 2007; Rübsamen et al, 2022; Sako et al, 2015; Sferruzza et al, 2021; Wang et al, 2019; Wang et al, 2020a; Wang et al, 2020b; Xu et al, 2016; Zhang et al, 2022; Zhao et al, 2019; Zhou et al, 2021).…”
Section: Meta‐analysesmentioning
confidence: 99%
“…There have been 33 meta‐analyses on the wealth of data on Nf as a biomarker for neurodegeneration over the past 15 years (Agah et al, 2018; Alagaratnam, Widekind, et al, 2021; Angelopoulou et al, 2021; Arneth & Kraus, 2022; Cai & Huang, 2018; Choong et al, 2019; Cong et al, 2021; Forgrave et al, 2019; Gao et al, 2020b; Ge et al, 2018; Hoiland et al, 2022; Hu et al, 2017; Jin et al, 2019; Karantali, Kazis, Chatzikonstantinou, et al, 2021; Karantali, Kazis, McKenna, et al, 2021; Katayama et al, 2020; Koychev et al, 2021; Li et al, 2016; Liu et al, 2022; Liu, Chen, et al, 2020; Martin et al, 2019; Mondello et al, 2021; Peng et al, 2022; Petzold et al, 2007; Rübsamen et al, 2022; Sako et al, 2015; Sferruzza et al, 2021; Wang et al, 2019; Wang et al, 2020a; Wang et al, 2020b; Xu et al, 2016; Zhang et al, 2022; Zhao et al, 2019; Zhou et al, 2021).…”
Section: Meta‐analysesmentioning
confidence: 99%
“…In addition to CSF, peripheral blood, cord blood, amniotic fluid, urine, saliva and, more recently, feces have been shown to contain detectable levels of S100B that are moreover significantly modified during several pathological conditions (Di Liddo et al, 2020;Gazzolo et al, 2005Gazzolo et al, , 2001aGazzolo et al, 2001bGazzolo et al, , 2000Guo et al, 1995;Kato et al, 1983). Thus, the S100B level in biological fluids has been extensively studied as a pathological biomarker, and are still the goal of active research and the object of recent extensive and valuable reviews (Bersani et al, 2020;Cardoso et al, 2018;Choong et al, 2019;da Rosa et al, 2016;Liang et al, 2019;Lorente, 2017). More recently, S100B has also been detected in the serum of patients affected by SARS-CoV-2 to correlate with the severity of the disease, thus broadening the range of disorders where the protein might be prospectively involved (Aceti et al, 2020).…”
Section: Biomarker and Active Factormentioning
confidence: 99%
“…A systematic review of 14 studies on 321 pts by Choong et al of biochemical markers in the assessment of SCI in TAA repair demonstrated a dramatic rise of S100B proteins, neurone-specific enolase (NFL) and glial fibrillary acidic protein (GFAp) in CSF which may be of use [282]. In contrast, Harky et al who also performed a systematic review found that there is a lack of high-quality studies investigating CSF biomarkers during TAA repair to detect SCI [283].…”
Section: Neurological Complications Including Spinal Cord Injurymentioning
confidence: 99%